Motivasi Berolahraga Masyarakat Jorong Air Balam Pada Masa Pandemi Covid-19 - Afelinus Zulukhu; Hanif Badri; Septri Septri; Andri Gemaini (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
Based on observations that have been made in Jorong Air Balam, the community does not seem interested in participating in sports activities. This may be due to the many factors that influence the community so that only a few people engage in sports activities.This research is descriptive research. The number of population members in this study was 1,358. The sampling technique in this research is to use incidental sampling technique. In this study, researchers took people who were met by chance and were willing to become respondents as samples in this study. In this study, it was found that the exercise motivation of the people of Jorong Air Balam during the covid-19 pandemic was in the high category with a value of 78. tall. Thus, it can be concluded that: (1) The motivation for exercising the people of Jorong Air Balam Nagari Preparation of Koto Tuo, Koto Balingka District, West Pasaman Regency during the Covid-19 pandemic in the high category, (2) Intrinsic motivation for exercising the people of Jorong Air Balam Nagari Preparation of Koto Tuo, District Koto Balingka, West Pasaman Regency during the Covid-19 pandemic in the high category, (3) Extrinsic motivation for exercising the people of Jorong Air Balam Nagari Preparation of Koto Tuo, Koto Balingka District, West Pasaman Regency during the Covid-19 pandemic in the high category